2018
DOI: 10.1007/s10694-018-0728-9
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Fire Resistance of Cross-laminated Timber (CLT)

Abstract: Cross-laminated timber, typical abbreviations CLT or XLAM, is currently one of the most innovative product in building with wood. This solid engineered timber product provides advantages compared to other solid timber slabs as the dimension stability, i.e. swelling and shrinkage, is controlled by the crosswise laminations. As for other components, the fire resistance has to be verified for this type of product. While fire testing is time consuming and costly, simulations provide flexibility to optimize the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…[14][15][16] However, it is known that the char rate is significantly affected by the severity of the fire exposure, and data on charring rates for nonstandard fire exposures have been limited to more recent studies related to the recent increase in interest in mass-timber buildings. [17][18][19][20] The lack of information on char rates under these conditions makes it difficult to perform fire resistance calculations under nonstandard fires. Recently, several full-scale fire tests on mass timber compartments have been conducted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] However, it is known that the char rate is significantly affected by the severity of the fire exposure, and data on charring rates for nonstandard fire exposures have been limited to more recent studies related to the recent increase in interest in mass-timber buildings. [17][18][19][20] The lack of information on char rates under these conditions makes it difficult to perform fire resistance calculations under nonstandard fires. Recently, several full-scale fire tests on mass timber compartments have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Others have found that the charring rate is proportional to the ratio of external heat flux divided by density . However, it is known that the char rate is significantly affected by the severity of the fire exposure, and data on charring rates for nonstandard fire exposures have been limited to more recent studies related to the recent increase in interest in mass‐timber buildings . The lack of information on char rates under these conditions makes it difficult to perform fire resistance calculations under nonstandard fires.…”
Section: Introductionmentioning
confidence: 99%
“…Fire safety is always an important issue in the development of these new generation massive timber materials. Current research believe that the fire behaviour of wood is predictable (Bisby and Frangi, 2015;Klippel and Frangi, 2017;Ostman et al, 2017;Schmid et al, 2018). International design codes, such as EN 1995EN -1-2:2004EN (2004 and CLT Handbook (FPInnovations, 2013), have provided design strategies to determine the fire resistance-engineered timber structures based on a simplified reduced cross section calculation methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Development of new timber based structural materials which provide producing of mass structural members enables to delete the limitation on the timber use for the multi-storey buildings. The mass timber structural members are characterized by the increased fire resistance in comparison with the light timber members with the small cross-sections (Green & Karsh, 2012;Green & Taggart, 2017;Nedryshkin, Gravit, & Grabovyy, 2018;Buka-Vaivade, Serdjuks, Goremikins, Pakrastins, & Vatin, 2018;Saknite, Serdjuks, Goremikins, Pakrastins, & Vatin, 2016;Schmid, Klippel, Just, Frangi, & Tiso, 2018). Construction of multi-storey timber buildings represent the most practical, effective and environmentally responsible solution to the global housing shortage which is caused by the increased urbanization and the densification of cities.…”
Section: Introductionmentioning
confidence: 99%